Social representations of family violence of police operators Metropolitan Lima - Oblitas Béjar, Beatriz (2014)
This is a preliminary qualitative study on social representations (SR) family violence (FV) of VF policemen serving in Lima Women Police Stations. Objective: To determine the VF RS policemen having women police stations in Lima. Methodology: Qualitative study of transversal in the world of police operators working in three women’s police stations and serve complaints about VF . Interview with 24 operators and the word association technique in group sessions informed consent was used. The data to descriptive and specific analysis of the relevant variables in the study underwent. The main results showed that the figurative nucleus or core of the RS of the VF is related to aggression and abuse as attributes associated beatings, insults, humiliations; observed a prevalence of psychological violence as a representative of family violence.